Developmental Coordination Disorder and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The prevalence, comorbidity, and outcome of "developmental coordination disorder (DCD)" were studied in 7-10 year-old children at the Department of Child and Adolescent Psychiatry, Sahlgren University Hospital, Goteborg, Sweden.